2000
DOI: 10.1038/sj.gene.6363667
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of susceptibility to UV-induced immunosuppression by interacting quantitative trait loci

Abstract: Ultraviolet B radiation (290-320 nm) initiates a dose and wavelength dependent down-regulation of cell-mediated immunity which is critical in experimental ultraviolet radiation (UV) carcinogenesis, preventing immune attack on highly antigenic UV-induced tumors. UV-induced immunosuppression has been demonstrated in humans and may be a risk factor for skin cancer. In this study, we have investigated genetic linkage of the autosomal loci controlling this trait. Previously, we had derived a model describing contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
1
21
1
Order By: Relevance
“…We have previously identified that the thymocytes proliferative response to anti-CD3 stimulation was significantly lower at young and old age in parental D2 mice compared to B6 mice. 6 Consistent with this, previous mapped QTLs close to our mapped Chr 10 region were mostly associated with immune regulation 30 and development of autoimmune diseases, 31,32 with two recent reports indicating that proximal to this region at Chr 10, 35 cM contains a QTL that is associated with agerelated tumor suppression and the regulation of lifespan in mice. 33,34 Thus, although we do not rule out the possibility that regulation of the value of thymic involution can be affected by the hormonal effects, at least in the B6, D2, and B Â D RI strains of mice, the development and regulation of T-cell response may be more important in influencing the thymic involution rate.…”
Section: Discussionsupporting
confidence: 70%
“…We have previously identified that the thymocytes proliferative response to anti-CD3 stimulation was significantly lower at young and old age in parental D2 mice compared to B6 mice. 6 Consistent with this, previous mapped QTLs close to our mapped Chr 10 region were mostly associated with immune regulation 30 and development of autoimmune diseases, 31,32 with two recent reports indicating that proximal to this region at Chr 10, 35 cM contains a QTL that is associated with agerelated tumor suppression and the regulation of lifespan in mice. 33,34 Thus, although we do not rule out the possibility that regulation of the value of thymic involution can be affected by the hormonal effects, at least in the B6, D2, and B Â D RI strains of mice, the development and regulation of T-cell response may be more important in influencing the thymic involution rate.…”
Section: Discussionsupporting
confidence: 70%
“…Repeating the similar procedure for case of equal prior probabilities; we can obtain the restricted MLEs of the two-locus recombination fractions correspondingly. An example Zhou et al (2008) analysed a real data set that comprises of 134 individuals from a backcross of mice (Clemens et al 2000). Here we use the proposed RPA to revisit that data set and estimate three two-locus recombination fractions among marker loci D2Mit365, D2Mit272 and D2Mit456 on the linkage map of chromosome 2.…”
Section: Cases For More Offspring and Unequal Prior Probabilities Of mentioning
confidence: 99%
“…After computation with the DS method, we obtain the estimates of QTL effects, many of which are zero in fact, and some significant main effects are same with those given in the literature [10]. Owning to this fact, we choose the most significant six main effects and the possible interacting loci to build a new statistical model to further detect the significant interacting loci.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…The data is from the literature [10]. Clemens et al [10] collected the genotype data on 64 SNPs and immunosuppression data of 134 backcross individuals, and they detected some main effects and interactions among these loci. Here we proposed a new strategy and found different genotype effects for the immunosuppression.…”
Section: Introductionmentioning
confidence: 99%